The Utility of Specific Antibodies Against SARS-CoV-2 in Laboratory Diagnosis - Fu, Yu; Pan, Yunbao; Li, Zhiqiang; Li, Yirong (Frontiers in Microbiology, 2021)
Abstract The Coronavirus Disease 2019(COVID-19) caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has now become a global pandemic due to its high transmissibility. Due to the unavoidable shortcomings of the traditional diagnostic assay: nucleic acid testing, diverse serological assays based on the humoral response to COVID-19 which are characterized by high-throughput, less turn-around-time, and less workload, is playing a more and more crucial role to supplement the nucleic acid test, better facilitating the containment and prevention of SARS-CoV-2. In this review, we summarize the dynamic change of the specific IgM, IgG and IgA antibodies against SARS-CoV-2 as well as neutralizing antibodies and discuss the clinical utility of the different serological testing assays and the limitations of serological assays in laboratory diagnosis. SARS-CoV-2, a newly discovered virus, shows some unique pathogenetic and epidemiological characteristics which have not been completely understood so far. Currently, studies about the antibody responses against SARS-CoV-2 and the clinical utility of serological testing of SARS-CoV-2 specific antibody are increasing. It’s well suggested that the combination of serological tests and nucleic acid tests can cohesively improve the testing proficiency for identifying COVID-19 suspected patients.